Religious Moderation as a Strategy for Student Competence Formation in Multicultural Schools: Moderasi Beragama sebagai Strategi Pembentukan Kompetensi Siswa di Sekolah Multikultural - Roni R Dabutar; Wahyudin Nur Nst; Mohammad Al Farabi (Universitas Muhammadiyah Sidoarjo, 2025)
General background: In a multicultural society like Indonesia, education plays a pivotal role in fostering tolerance and preventing radicalism. Specific background: SMA Negeri 1 Sidikalang, with its diverse religious and cultural composition, serves as a strategic setting to implement religious moderation in education. Knowledge gap: However, studies on how religious moderation is operationalized in rural multicultural public schools remain limited. Aims: This study aims to examine how values of religious moderation are integrated into Islamic and Christian Religious Education to shape students’ competencies holistically. Results: Using a qualitative-descriptive approach, findings show that moderation is embedded through curriculum design, teacher role modeling, inclusive extracurricular activities, and community collaboration, resulting in students’ enhanced empathy, tolerance, and respect for diversity. Novelty: This study uniquely maps the enabling and inhibiting factors of religious moderation in a rural public high school, revealing its positive influence across spiritual, social, and academic domains. Implications: The research underscores the importance of institutional support, experiential learning, and interfaith dialogue in building inclusive educational environments aligned with the values of Pancasila and the Merdeka Curriculum.Highlight : Religious moderation is integrated into teaching through contextual and dialogic learning. Teachers serve as role models, promoting tolerance and empathy across religious lines. School activities and institutional policies support inclusive values and multicultural harmony. Keywords : Religious Moderation, Religious Education, Tolerance, Contextual Learning, Student Competence